Bettencourt-Saint-Ouen (Somme) Cinq occupations paléolithiques au début de la dernière glaciation - Locht, Jean-Luc (Documents d'archéologie française, 2002)
Situated in the North of France, Bettencourt-Saint- Ouen is an open-air Middle Palaeolithic site, most probably used as a hunters' stopping place. Five successive phases of occupation have been excavated, covering a period of 40.000 years Study of the site has revealed fondamental data lot our understanding of human occupation, as well as important informations on environmental changes to the site during the final glacial period (from the Eemian Interglacial to the lower Weichselian Pleniglacial). Distribution of finds at Bettencourt, coupled with the technology and typology of the site's lithic industries, point to a continuity in systems of production and cultural traditions from 112,000 to 68,000 BP.